JOHN BOWLBY THEORY AND THE MENTAL HEALTH ISSUES OF CHILDREN - Muazzamxon Isakova Tulkinovna; Abdullayeva Zeboxon Odiljonovna (Journal Park Publishing, 2025)
John Bowlby’s attachment theory emphasizes the necessity for children to establish a secure and consistent bond with their parents or caregivers. According to his theory, it is crucial for children to form a strong attachment with their primary caregiver to feel secure, develop self-confidence, and successfully navigate the social world. The socio-psychological aspects of this theory influence a child's mental health, as the formation of secure attachment fosters self-confidence, emotional stability, and successful integration into society. This scientific analysis focuses on exploring the significance of Bowlby’s attachment theory in relation to children's mental health.
Keywords: John Bowlby, attachment theory, child mental health, socio-psychological aspects, secure attachment, emotional stability, psychological security, mental illness, attachment, fear, anxiety, trust, stress, neurosis.